Statistical Appraisal of Urban Growth in Barmer District (RAJASTHAN) - Gupta, B S; Purohit, M L; Kumar, Pramod (Annals of Arid Zone, 2016)
The path coefficient and multiple regression analyses revealed percentage literacy and population. followed by percentage of non-agricultural workers, as the crucial variables for urbanization in Barmer district. Step-up regression analysis determined the major contributors to urbanization as percentage literacy, followed by population, percentage of non-agricultural workers, population density and infrastructure facilities. The high values of coefficient of determination (R2 = 55.77%) implied that the estimated regression equations could safely be used for planned growth of urbanization in arid areas.